Pemanfaatan Marketplace Shopee sebagai Media Promosi pada Pelaku UMKM di Desa Kaliwlingi, Kabupaten Brebes - Nur Hidayah Fasihah; Hendri Sucipto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The current development of MSMEs has an effect on increasing people's income. However, the lack of access to promotion in marketing causes MSMEs to experience problems in increasing income. This problem can be overcome by digitizing MSMEs which are expected to be able to promote their products online, one of which is by providing assistance by making a Google map. This community service aims to provide knowledge to MSME business actors about the importance of promotion in the world of digitalization. Thus, KKN students carry out community service to fully support MSMEs in the village of Kaliwlingi, Brebes Regency so that MSME Business Actors can compete broadly in the outside realm of their area. This service starts from the preparation stage by visiting MSMEs through door to door, and continues with training on making Shopee for each MSME business actor.